The Development of Social Characteristics of Children in Siti Hajar Kindergarten - Rivani Putri Junais, Virly; Hunta, Nurhayati; Bakari, Fitriyah Ningsi R; Mohamad, Ayu Kartika; Gobel, Delsi D. (PT Literasi Nusantara Publisher, 2022)
The development of children's behaviour in adjusting to the rules of society where the child is. Social development is obtained by children through maturity and learning opportunities from various responses to themselves. The basis of emotions is the body and physiological conditions. Thus, emotions will affect perception, thinking, and behavior. Emotions can be expressed through language, facial expressions, and body language. Emotions can be a driving force for someone to do certain activities. Based on the opinion of experts, it can be concluded that emotion is a reaction that includes physiological changes, behavioral expressions, and changes in feelings due to an incident that a person experiences when facing a certain situation.